Iron status nutrition in Brazilian elite male judoist - Portella, E. S.; Koury, J. C.; Donangelo, C. M. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Factors as intensity, duration, exercise type and iron intake can affect elite athletes' hematological indicators (SPEICH et al, 2001 ). The purpose of this study was to compare the effect of the iron intake of Brazilian elite male judoist before and after nutritional orientation. Methods The study protocol was approved by the Ethical Committee of Pedro Ernesto University Hospital, Rio de Janeiro, Brazil. Male senior elite judoist athletes (n=9) were regular participants in regional and international competitions. None of the athletes used supplements of vitamins or minerals during at least 6 months prior to participation in the study. The athletes were instructed not to eat for 10 h before sample collection. Blood samples (10 ml) were obtained in the morning (8:00 AM) by venous puncture. Aliquots of whole blood were obtained for determination of packed-cell volume (HT), hemoglobin (HGB), erythrocyte counting (RBC), volume medium corpuscular (VMC), medium corpuscular hemoglobin (MCH), plasma iron (Fepl) and total iron binding capacity (TIBC) analysed by conventional methods. The iron intake was evaluated through the 24 hours recall method, applied twice, being before and 30 days after the nutritional orientation. The quantification of the iron intake was accomplished through the Brazilian Nutrition Support Program ( PROGRAMA..., 1993 ). Results/Discussion Analysis of the diets revealed that the judoist consumed significantly less iron heme (p=0.007) before the dietary orientation, however the macronutrients intake was, on average, appropriate. After 30 days of the dietary orientation the values of plasma iron increased significantly, TIBC also increased significantly ( SACHER & McPHERSON, 2002) . HB, HT, VMC, MCH and RBC did not alter of the first for the second nutritional orientation (Table 1), appears to be short period of time elapsed among the nutritional orientation. Significant and strong positive correlation found between dietary iron intake and plasma iron (r=0.85; p=0.005) and total protein intake (r=0.71; p=0.05). Conclusion The obtained results demonstrated the importance of the nutritional orientation for the maintenance of the iron nutritional status in elite judoist.